Answer:
- To determine the inverse of the given function,
Change f(x) to y , switch x and y , and solve for y.
- The resulting function may be written as:
[tex]f^{-1}x=\dfrac{\ln (x+4)}{2}[/tex]
Step-by-step explanation:
We know that while finding the inverse of a function the following steps are to be followed:
- Then we interchange x and y in the expression.
- and then we finally solve for y.
We are given a function f(x) by:
[tex]f(x)=e^{2x}-4[/tex]
Now, we put
[tex]f(x)=y[/tex]
i.e.
[tex]e^{2x}-4=y[/tex]
Now, we interchange x and y as follows:
[tex]e^{2y}-4=x[/tex]
and finally we solve for y
i.e.
[tex]e^{2y}=x+4[/tex]
Taking logarithmic function both the side of the equation we get:
[tex]2y=\ln (x+4)\\\\i.e.\\\\y=\dfrac{\ln (x+4)}{2}[/tex]
i.e.
[tex]f^{-1}x=\dfrac{\ln (x+4)}{2}[/tex]